Digital drawing for designers a visual guide to AutoCAD 2015 - Seidler, Douglas R (New York Fairchild Books, an imprint of Bloomsbury Publishing PLC, 2014)
"Created specifically to help designers master AutoCAD, "Digital Drawing for Designers 2014" is neither overly simplistic nor excessively technical, and teaches by relating to what architects and interior designers understand best: the visual world. Beginning with the building blocks of drawing (lines, circles, and arcs), the book progresses through architectural graphic standards, enabling students to create drawings that effectively communicate their design ideas. Advanced features such as annotative dimensions, annotative blocks, express tools, and linking drawings (XREFs) are also covered. Instructions are illustrated using language and concepts from manual drafting, facilitating a smooth transition to the digital environment for all designers. New learners will appreciate the step-by-step lessons and visual illustrations, while experienced design professionals can easily access material to refresh their knowledge. Clear, concise, and above all visual, this AutoCAD guide speaks directly to the needs of architects and interior designers"--
Machine generated contents note: -- Part 1: Hand Drawing and Digital DrawingChapter 1: Digital Drawing ToolsChapter 2: Drawing Lines and ShapesChapter 3: Modifying Lines and ShapesChapter 4: Drawing with Accuracy and SpeedPart 2: Design DrawingsChapter 5: Organizing Plans, Sections and ElevationsChapter 6: Drawing and Printing to ScaleChapter 7: Text Styles and SizesChapter 8: Hatches and Dashed LinesPart 3: Advanced Drawing ToolsChapter 9: Stencils and BlocksChapter 10: Advanced Editing ToolsChapter 11: Dimensioning Your DrawingChapter 12: Text LeadersChapter 13: Drawing Symbols and Attributed TExtChapter 14: Lining Drawings/External ReferencesChapter 15: AutoCAD WS on your iPhone, iPad and Android Device
Includes index
Keywords: AutoCAD; Computer-aided design; ARCHITECTURE / Urban & Land Use Planning